PERBANDINGAN ANALISIS PERHITUNGAN VARIASI DIAMETER PULLEY 80 MM DENGAN 100 MM PADA PENGGERAK MESIN JAHIT SUNSTAR KM-250B DI CV YAMINA INDAH LESTARI KUNINGAN - Cecep Nana Nasuha; Uyu Wahyudin; Mohamad Galih Hamka (Jurnal Fakultas Teknik Kuningan, 2023)
The Sunstar KM 250-B sewing machine uses pulley and belt drive system components, as well as a driven shaft, the driving source uses a motor clutch type dynamo. The speed of the machine is very important to the results of production. Therefore it is necessary to have a calculation with the exact variation in the diameter of the drive pulley. The purpose of this study is to find out the comparison of the analysis of the calculation of pulley diameter variations with the calculation of shaft rotation, torque, calculation of belt / belt length and belt around speed / belt, The method used in this study is to use quantitative methods, namely measuring, observing and calculating machine specifications, the research data obtained in the form of numbers. Then analyze the data. The results of the study were obtained with a Pulley Diameter of 80 mm = Rotation of the sewing machine shaft 2288 rpm, Sewing Machine Torque 0.0010 N.m, Belt / belt length 108.485 cm, Belt / belt circumference speed 11.97 m / s while pulley diameter 100 mm = Sewing machine shaft rotation 2860 rpm, Sewing Machine Torque 0.0008 N.m, Belt / belt length 151.4 cm, Belt / belt circumference speed 14.96 m / s